Preference Consistency: Veteran and Non-Veteran Nursing Home Resident Self-Reported Preferences for Everyday Living - Curyto, Kimberly (J Gerontol Nurs, 2020)
Understanding patient preferences is core to person-centered care. The consistency of everyday preference reporting was assessed comparing responses of Veteran (VA) and non-VA nursing home (NH) residents on the Preferences for Everyday Living Inventory (PELI) at baseline and 5 to 7 days later. Non-VA NH residents demonstrated higher perfect agreement than VA residents (66% vs. 56%, respectively) and higher acceptable agreement (95% vs. 88%, respectively). Multiple regression analyses examined significant predictors of reliability using demographics, cognitive functional variables, and interviewer ratings. In the VA group, higher perfect agreement was associated with residents who were less likely to have hearing deficits, better cognition, and better interviewer ratings related to energy, attention, and comprehension. In the non-VA group, higher perfect agreement was associated with residents who were younger and more independent with walking. Overall, higher agreement was associated with being female, non-VA, and having better cognition. Implications for future research and clinical practice are highlighted.